A rare case of polydactyly with multiple defects - Kumar, Sanjeev; Bansal, Pradeep Kumar; Ishran, Rohit; Kasana, Rajendra (International Journal of Advances in Medicine, 2020)
Bardet-Biedl Syndrome (BBS) is a very rare genetically heterogenous disorder. Here is a case of 27 yr. old obese male presented with acute gastroenteritis with shock in our department. He had polydactyly in both upper limb and left lower limb, blindness since childhood, with difficult in learning and delayed onset of milestones. Patient’s sibling (younger brother 20-year-old) also had same problems since childhood and one female baby died within few days of birth. He was having single testis. Patient was managed conservatively. The available literature on this syndrome was reviewed.